Characteristics of Electric Current in The Electrolysis of Acid and Alkaline Water Production for Health - Kurniawan, Ekki; Raharjo, Jangkung; Manfaati, Rintis; Yulinda, Yulinda (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2025)
Acidic and alkaline water with potential health benefits can be produced through the process of electrolysis. In addition to the applied voltage, electric current is a crucial parameter in the electrolysis process. The energy consumed during electrolysis can be determined by measuring the voltage, electric current, and duration of operation. This study aims to investigate the characteristics of electric current during the electrolysis of mineral water to produce Electrolyzed Reduced Water (ERW) and Electrolyzed Oxidized Water (EOW), commonly referred to as alkaline and acidic water, respectively. The electrolysis current is monitored at specific time intervals (0, t₁, and t₂) throughout the process. In the initial stage (from 0 to t₁), the current increases exponentially, similar to the charging current behaviour of an inductor (L). In the second stage (from t₁ to t₂), the current decreases exponentially, resembling the discharge of a capacitor (C). In the final stage (after t₂), the current stabilizes and remains nearly constant, analogous to current flow through a resistor (R). A novel aspect of this study is the introduction of an equivalent RLC transient circuit model to describe the dynamic behaviour of electrolysis current. In this model, the electrolysis process is represented by a series RLC circuit with a switch operating sequentially at 0 (inductor charging), t₁ (capacitor discharging), and t₂ (resistive steady state). To the best of our knowledge, this RLC-based interpretation of electrolysis current behaviour in the context of ERW and EOW production has not been previously reported.